Fabrication of mini hydroelectric generator / Muhammad Firdaus Rashidy - Rashidy, Muhammad Firdaus (2022)
Hydroelectric is a renewable energy that converts the kinetic energy of flowing water into electricity. Today, hydropower accounts for approximately 16% of global electricity production. Although electricity is essential for daily life, there are still places where it is unavailable, such as for people living in rural areas. Currently, 940 million people (13 percent of the world's population) do not have access to electricity. Therefore, the objective of this project is to design and analyze a mini power generator that reduces the cost and size to make it more versatile and easier to use by anyone. The methodologies used are by searching the existing product and study on how it works. After finding on how it works and what formula to use, three concept designs were made. Then, one of the concept designs is chosen. The concept is designed in Solidwork. The expected result is the project being able to generate electricity.